DAMPAK DRAMA KOREA SEBAGAI MEDIA PROMOSI PRODUK KECANTIKAN TERHADAP PASAR DI INDONESIA - Vanessa Bernadette Louise; Rizqi Muttaqin (LPSDI Bina Patria, 2024)
This research aims to explore and explore whether Korean dramas are proven to have an influence on the market in Indonesia, so that many people in Indonesia are interested in buying products contained in Korean dramas. The problem raised in this research is whether Drakor is good for promotional media. Korean dramas (drakor) can have a positive impact on promotional media, especially Korean dramas have a significant impact as promotional media, both for Korean products and tourism destinations. This has become an effective tool in introducing and marketing Korean culture to a global audience. The author's current research method uses quantitative methods. Through interview data collection techniques, it can be concluded that Korean dramas influence product promotion media. This was proven when conducting an interview with one of the Korean drama viewers. When watching a Korean drama series, the first thing they saw was the beauty product used by the main character. One of the Korean Drama viewers also learned about beauty products that he didn't know about before through the Korean Drama series